Wage determination and compensating wage differentials in the informal sector: A quantile regression with multi-level sample selection - Pisit Leeahtam (2018)
This study investigates Chiang Mai informal workers' wage determination in the equilibrium focusing on the compensating wage differential from taking occupational hazard risks with the presence of unemployment risk. Since there is a substantial heterogeneity among different groups within the informal sector, this study applies the quantile regression analysis with multi-level sample selection. The results show evidences for the compensating wage differentials in the lower and middle quantiles, but not the higher quantiles. The introduction of the unemployment risk variable into the wage equation proves the significance of the job mobility assumption. With unemployment risk, the workers not only are not compensated for their occupational hazards, but also face with an inefficient job matching outcomes. This emphasizes the significant spill-over benefit from the improvement of the job mobility condition. © Springer International Publishing Switzerland 2014.